PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PENGAWASAN TERHADAP PENGELOLAAN ANGGARAN BERKONSEP VALUE FOR MONEY PADA INSTANSI PEMERINTAH (Studi Empiris SKPD Provinsi Riau) - Debi Putri Pertiwi; Raja Adri Satriawan; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research aims to examine the influence of accountability, transparency, and and control to budgeting management of the value for money concept of government institute in Riau Province. The research population of all employees echelon 3 & 4 in the local government SKPDs Riau Province. The data of this research were obtained from questionnaires. The sample used by 86 respondents were selected using purposive sampling and analyzed using multiple regression with Software SPSS for Windows Version 19. The results showed that accountability, transparency, and and control to budgeting management give a effect to the budgeting management of the value for money concept of goverment Institute.Keywords: Accountability, Transparency, Control, Budgeting management of the value for money concept